2012
DOI: 10.1080/17450128.2011.647773
|View full text |Cite
|
Sign up to set email alerts
|

Reducing sexual risk taking behaviors among adolescents who engage in transactional sex in post-conflict Liberia

Abstract: Transactional sex (TS) has been correlated with HIV/STD infection, pregnancy, early marriage, and sexual violence in sub-Saharan Africa (SSA). Few Western-based HIV prevention programs adapted for SSA have examined intervention impacts for this group. This article examines whether an HIV prevention intervention, delivered to sixth-grade students in Liberia (age range 14–17) and found to increase condom use and other mediators for the larger sample, significantly impacted sexual behaviors and mediators for thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 24 publications
3
29
2
Order By: Relevance
“…Eight papers reported HIV and/or STI knowledge, attitudes and behavior results following HIV prevention programs. Two papers reported on a group randomized controlled trial to evaluate the impact of an evidence-based HIV prevention intervention on sexual risk behaviors of in-school 6 th graders in Liberia [ 35 , 36 ], and six used post-intervention surveys to assess program effectiveness in four African countries [ 37 - 42 ]. All of the papers reported mixed results of their prevention programs regarding some elements of knowledge and behavior change; however, the four that follow reported more positive results.…”
Section: Resultsmentioning
confidence: 99%
“…Eight papers reported HIV and/or STI knowledge, attitudes and behavior results following HIV prevention programs. Two papers reported on a group randomized controlled trial to evaluate the impact of an evidence-based HIV prevention intervention on sexual risk behaviors of in-school 6 th graders in Liberia [ 35 , 36 ], and six used post-intervention surveys to assess program effectiveness in four African countries [ 37 - 42 ]. All of the papers reported mixed results of their prevention programs regarding some elements of knowledge and behavior change; however, the four that follow reported more positive results.…”
Section: Resultsmentioning
confidence: 99%
“…Other factors simply provide opportunities for sexual practice and are related to risky sexual behaviors, such as those in a romantic relationship [15,19]. While these other factors have been related to risky sexual behaviors, studies have shown even controlling for these important precursors, one particular factor still has a strong relationship with risky sexual behaviors-sexual content in the media or sexually explicit media (SEM) [20][21][22]. Strasburger et al [23] concluded sexual content in the media is a significant factor that influences children and teens in sexually-related behaviors, attitudes, and believes.…”
Section: Introductionmentioning
confidence: 99%
“…Velezmoro and colleagues [65] have argued that studying sexual expression in different cultural settings sheds much light on the similarities and differences of the same phenomenon across cultures. Furthermore, some Asian countries suffer from increasing prevalence of STIs, such as an increased rate of HIV infection among young population in China [53,66] and South Korea [67] and both HIV and other STIs (e.g., gonorrhea) are at their highest rates among adolescents and young adults (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) in Taiwan [8]. Although a few studies have been conducted and yielded similar results, these studies also suffered from the aforementioned limitations [68,[53][54].…”
Section: Introductionmentioning
confidence: 99%
“…No study provides effects for adolescents with physical disabilities, for adolescent first-time parents or for adolescent sex workers. For this last category, we did not include the study that focused on girls who had engaged in transactional sex at least once in the past (Atwood et al 2012a). …”
Section: Categories Without Evidencementioning
confidence: 99%